GROWTH PERFORMANCE OF CATFISH SEEDS (Pangasius sp.) WHICH IS GIVEN AN ANTHILL TUBER EXTRACT - Djauhari, Ricky; Simamora, Vera Natalia; Christiana, Ivone (Journal of Fish Health, 2021)
The use of probiotics, prebiotics and aquaculture synbiotics is widely applied to aquaculture intensification as control agents. Three species of endophytic bacteria were found, namely Bacillus sp. (1), Bacillus sp. (2), and Bacillus pumilus which is associated with anthill plants and can produce antioxidant compounds. This study aims to evaluate the growth performance of catfish fry (Pangasius sp.) given ant nest tuber extract. In this study, ant nest tuber extract was mixed into feed using the coated method in doses of 0% (A), 1% (B) and 2% (C). Fish with an initial body weight of 2.00-3.17 g were kept in three ponds with a total of 9 nets measuring 1x1x1 (m 3) (30 fish/nets), is 3 nets placed in each pond. Fish were fed treatment with three replications for 30 days. The results of this study are the average final biomass weight of catfish ranging from 8.75 to 22.17 g, in all treatments not significantly different from K. The average value of JKP, RKP, EP, LPH and Wg obtained on administration of the doses of 1% and 2% ant nest tuber extract were not significantly different for K. The highest amylase enzyme activity and feed efficiency were found in the catfish fry group that consumed feed supplementation with 1% ant nest tuber extract, each of 9.537 IU/mL. and 102.57% and the least feed consumption, namely 443.33 g. It can be concluded that the best dose of ant nest tuber extract which produces amylase enzyme activity and the highest feed efficiency is found in the catfish fry group that consumes feed supplementation with 1% ant nest tuber extract.